Comparative karyotype analysis and chomosomal characterization of Lycopersicon esculentum Mill. - Warasy, Ashma Ahmed (Jahangirnagar University Journal of Biological Sciences, 2025)
Lycopersicon esculentum Mill. a member of the Solanaceae family was examined following orcein staining. The analysis revealed that, interphase nuclei and prophase chromosomes represented a simple chromocentric and gradient type in BARI Tomato-11 and -15, respectively. They were identified as having been 2n = 24 chromosomes. The chromosomal length ranged from 0.87–1.56 μm in BARI Tomato-11 and from 0.78–1.32 μm in BARI Tomato-15. The total chromosome length of 2n were 28.29 μm for BARI Tomato-11 and 25.14 μm for BARI Tomato-15. The centromeric formula was determined to be 18m+6sm in BARI Tomato-11 and 24m in BARI Tomato -15. No gradual decrease in chromosome length was observed in either variety. However, the range between the highest to lowest chromosome length was greater in BARI Tomato-11 compared to BARI Tomato-15. The presence of exclusively metacentric chromosomes and the absence of gradual decrease of chromosome length in BARI Tomato-15 suggest its primitive karyotypic nature . In contrast, the combination of metacentric and submetacentric chromosomes in BARI Tomato-11 indicates a relatively more advanced chromosomal architecture . These karyotypic characteristics clearly distinguish BARI Tomato-11 and BARI Tomato-15 at the cytogenetic level. Jahangirnagar University J. Biol. Sci. 13(1 & 2): 55-61, 2024 (June & December)